METABOLITE PROFILING OF MORINGA USING PY-GCMS AND TOLERANCE EVALUATION TO ALUMINUM ON IN VITRO CULTURE - Rudiyanto Rudiyanto; Agus Purwito Purwito; Darda Efendi; Andri Martin (SEAMEO BIOTROP, 2025)
Article Highlight: Four accessions of Moringa oleifera from different regions in Indonesia were evaluated to identify with tolerance to aluminium (Al) stress Eight metabolites show a very high correlation with acetic acid (one of the metabolites associated with AlCl3 stress) including cyclopentene, 2-allyphenol, 4-ethynyl-6-8-dioxane, vinyl ether, ethanone 1-oxiranyl, 2-methylpyridine, 2-butanone, and ethanesulfonic acid. This research makes a significant contribution to understanding aluminium tolerance in oleifera by identifying tolerant accessions, clustering relevant traits, and highlighting key metabolites to in vitro culture. ABSTRACT Moringa oleifera Linn. has received substantial scientific interest due to its numerous bioactive compounds and its function as a nutritional resource. The absorption of aluminum by plants hinders several metabolic and physiological processes, leading to inhibited plant development and decreased agricultural output. Some accessions from different regions in Indonesia were evaluated to identify those with tolerance to aluminum (Al) stress. Al-tolerant selection was carried out in vitro through the selection method for Al stress by adding 0, 50, 100, 250, and 500 mg/L of AlCl3 to the media. Furthermore, identifying the metabolite profile of four M. oleifera accessions from four distinct regions in Indonesia: Blora, Bogor, Enrekang, and Bima, has been done using Py-GCMS. Specific metabolites associated with tolerance to Al stress and organic acids need to be identified. The highest survival rate was observed in the Bogor and Blora accessions when exposed to AlCl₃ at concentrations ranging from 0 to 250 mg/L, demonstrating greater tolerance to AlCl₃ than other accessions based on various variable, such as shoot height, number of shoots, number of petioles on a medium containing 100 to 250 mg/L of AlCl₃. The mean value was not statistically different from the control. Acetic acid was identified as one of the metabolites associated with AlCl₃ stress. A total of 21 metabolites were specifically correlated with acetic acid in a positive manner, among which 8 metabolites including cyclopentene, 2-allyphenol, 4-ethynyl-6-8-dioxane, vinyl ether, ethanone 1-oxiranyl, 2-methylpyridine, 2-butanone, and ethanesulfonic acid exhibited a very high correlation.